PENGAMBILAN KEPUTUSAN PERNIKAHAN PADA GENERASI MILENIAL: PERSPEKTIF TEORI EKOLOGI BRONFENBRENNER - Prika Lisa Fahrani (Jurnal Riset Multidisiplin Edukasi, 2025)
Marriage is a crucial stage in one's life, described as a dream for many to achieve happiness, offering various benefits such as faith, offspring, social support, as well as peace and well-being. This study aims to understand the complexity of marriage decision-making among millennials from the perspective of Bronfenbrenner's Ecological Theory. The underlying is that marriage decisions are influenced by the interaction of various environmental systems. The research subjects were six millennial individuals (three married couples) aged 28-43 years, residing in Bali. The methodology employed was qualitative with a case study approach, involving in-depth interviews and thematic data analysis. The results indicate that millennial marriage decisions are influenced by five ecological systems: microsystem (immediate family, peers), mesosystem (inter-family interactions), exosystem (work environment, economy), macrosystem (cultural values, religion, social expectations), and chronosystem (changes over time). Emotional and financial support, family harmonization, economic conditions, cultural norms, and individual readiness over time are key influencing factors.